Penanggulangan Tindak Pidana Pengeroyokan Antar Warga Desa Sirih Sekapur dan Desa Pulau Jelmu oleh Kepolisian Sektor Jujuhan - Hartono, M. Rudi; Aditama, Ryan; Purba, Irma Hendriani (Universitas Batanghari Jambi, 2024)
A mass attack is a series of demonstrations of crimes carried out jointly by a group that cause non-physical or real harm resulting in injury or befalling someone. In this study the author touches on the Elucidating Scientific strategy, which is a technique that is able to obtain top to bottom information on an event that focuses on cycles and collaborates directly with the item being researched to obtain a broad and precise picture and will. reach a decision, and use Purposive Testing techniques, namely deciding on rarely chosen tests that involve special considerations according to the exploration objectives. Judging from the in-depth investigation, we can conclude that the wrongful act of beatings is remembered as a violation of the community's request as stated in Article 170 of the Criminal Code, where the number of wrongful acts of beatings is due to individual problems between two young people in the city, thus leading to beatings including every inhabitant of the city. This study aims to find out in more depth the efforts to suppress criminal demonstrations of beatings between residents of Sirih Sekapur City and Jelmu Island City carried out by the Jujuhan Police, Cairo Bungo, the deterrence of which is traced in the handling of criminal demonstrations of beatings and efforts to suppress them. Obstacles in handling criminal demonstrations include beatings between residents. Sirih Sekapur City and Jelmu Island City by Jujuhan Police, Bungo Regency. The exploration technique used is exact juridical testing with a social legitimacy exploration approach and a case approach. The information gathering strategy uses interviews. The end of this examination was that the Jujuhan Police, in handling criminal demonstrations of beatings between city residents, carried out training such as sambang, guiding, supervising, monitoring gang training, and fostering good relations between residents by holding football matches. The obstacles faced by the Jujuhan Police in handling criminal demonstrations of beatings between residents were a pessimistic attitude towards the police, the ease of being initiated by the community, and the absence of police. Regarding efforts to overcome obstacles, the Jujuhan Regional Police adopted an interesting strategy, collaborated with the city government, and expanded relief efforts by collaborating with individuals from the police force.